Different Varieties of Uncertainty in Human Decision-Making - Bland, Amy R.; schaefer, alexandre (Frontiers in Neuroscience, 2012)
The study of uncertainty in decision making is receiving greater attention in the fields of cognitive and computational neuroscience. Several lines of evidence are beginning to elucidate different variants of uncertainty. Particularly, risk, ambiguity and expected and unexpected forms of uncertainty are well articulated in the literature. In this article we review both empirical and theoretical evidence arguing for the potential distinction between three forms of uncertainty; expected uncertainty, unexpected uncertainty and volatility. Particular attention will be devoted to exploring the distinction between unexpected uncertainty and volatility which has been less appreciated in the literature. This includes evidence from computational modelling, neuromodulation, neuroimaging and electrophysiological studies. We further address the possible differentiation of cognitive control mechanisms used to deal with these forms of uncertainty. Particularly we explore a role for conflict monitoring and the temporal integration of information into working memory. Finally, we explore whether the Dual Modes of Control theory provides a theoretical framework for understanding the distinction between unexpected uncertainty and volatility.